Odwołania do twórczości Seneki Młodszego w „Historycznym opisie miasta Szczecina” Paula Friedeborna - Cieśluk, Małgorzata (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
This article focuses on Latin quotations and paraphrases derived from the works of ancient authors that were incorporated by Paul Friedeborn into his chronicle of Szczecin, published in 1613. The aim of this study is to identify the sources from which Friedeborn drew the aforementioned excerpts. The analysis is based on passages taken from the works of Seneca the Younger, the ancient author cited most frequently in Friedeborn’s chronicle. Comparative analyses were conducted on more than 50% of the total number of Seneca quotations, considering two types of potential sources. First, they were compared with the text of selected editions of Seneca’s works published in the 16th and early 17th centuries. Next, the assumption that Friedeborn used intermediary sources was examined. This category includes narrative works from the period preceding the composition of the Szczecin chronicle, in which quotations from Seneca were employed in a manner analogous to Friedeborn’s approach (Hausbuch by Joachim von Wedel and Horologium principium by Antonio de Guevara). The analysis also takes into account popular collections of quotations, or commonplace books (Polyanthea by Domenico Nanni Mirabelli and a later edition of this collection edited by Joseph Lang). The results confirm that Friedeborn relied on intermediary sources for his quotations from Seneca, suggesting that he may have used a similar method to obtain excerpts from other ancient authors.